2006
DOI: 10.1093/deafed/enl018
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Technical Signs in Science: Implications for Lexical Database Development

Abstract: Both classroom instruction and lexical database development stand to benefit from applied research on sign language, which takes into consideration American Sign Language rules, pedagogical issues, and teacher characteristics. In this study of technical science signs, teachers' experience with signing and, especially, knowledge of content, were found to be essential for the identification of signs appropriate for instruction. The results of this study also indicate a need for a systematic approach to examine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…It is then, once the language is understood that the child can synthesize this information and use it to formulate arguments about new scientific concepts presented. Lang et al (2007) also found that misconceptions can develop through the interpretation of signs. In their study they found that students were often unaware that the sign used in class represented a concept previously taught.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…It is then, once the language is understood that the child can synthesize this information and use it to formulate arguments about new scientific concepts presented. Lang et al (2007) also found that misconceptions can develop through the interpretation of signs. In their study they found that students were often unaware that the sign used in class represented a concept previously taught.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Not all deaf students use a signed language and of those that do, their sign language comprehension is often not at a high enough level cognitively for them to make full use of it when learning (Marschark et al, 2009). Lang et al (2007) identify that of all the key words used in science education, around 60 per cent do not have a signed representation and instead rely on finger spelling for identity. This can have implications on the conceptual understanding of a scientific concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because course content was not addressing the needs of teachers of the deaf. Lang et al (2007) argued that an indication that professional working with the deaf meets with difficulties is seen in a receipt of constant flow of queries for assistance on a daily basis from a variety of educators and students requests for assistance. The range includes planning professional development workshops in school districts for special teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Findings also begin to show that its use can support several of the "highly cited practices" for science and mathematics instruction for students who are deaf or hard of hearing (Easterbrooks & Stephenson, 2006). For example, building on research conducted by Lang, et al (2007) showing that conceptually accurate signing in science was able to provide greater science understanding, teachers who use the SMD may be able to integrate more conceptually accurate signs for mathematics terms into their math instruction to provide greater mathematics understanding (Practice 1: Teacher as Skilled Communicator, Practice 2: Instruction through the Primary Language). Also, use of multimedia technology may increase attention through use of imagery and promote retention during academic tasks (Easterbrooks, 2010).…”
Section: Implications For Practicementioning
confidence: 90%